Pengaruh Penerapan Knowledge Management dan Pengembangan Sumber Daya Manusia terhadap Kinerja Karyawan PT Telkom Tbk. (Studi Explanatory Survey pada Karyawan Unit Human Capital Management PT Telkom Tbk.) - Anggapraja, Indra Taruna (Universitas Brawijaya, Indonesia, 2016)
The aim of this study was to determine the effect of the application of Knowledge Management and HRM on Employee Performance PT Telkom Tbk. The data collected from questionnaires distributed to 61 respondents. Then, the data analyzed using the Path Analysis. Partial test results on the effect of Knowledge Management application on employees' performance amounted to 31.20%, it means that for 31.20%, the changing of employees' performance in Human Capital Management unit of PT Telkom Tbk. can be explained by the knowledge management application. The magnitude of the effect on the Human Resources Development on employees' performance is 33.37%, it means that for 33.37%, the changing employees' performance in Human Capital Management unit of PT Telkom Tbk. can be explained by the Human Resource Development. In the other hand, the results of simultaneous testing on the effect of Knowledge Management application and Development of Human Resources on employees' performance amounted to 64.57%. This means that 64.57% the changing of employees' performance in the Human Capital Management PT Telkom Tbk. can be explained by the variable on Knowledge Management application and Human Resource Development, while the remaining 37.0% is influenced by other factors